[Be3(μ3-O)3(MeCN)6Be(MeCN) 3 - Puchta, Ralph; Neumüller, Bernhard; Dehnicke, Kurt (Zeitschrift für Anorganische und Allgemeine Chemie)
Single crystals of [Be3(μ3-O)3(MeCN) 6Be(MeCN)33](I)6·4CH 3CN (1·4CH3CN) were obtained in low yield by the reaction of beryllium powder with iodine in acetonitrile suspension, which probably result from traces of beryllium oxide containing the applied beryllium metal. The compound 1·4CH3CN forms moisture sensitive, colourless crystal needles, which were characterized by IR spectroscopy and X-ray diffraction (Space group Pnma, Z = 4, lattice dimensions at 100(2) K: a = 2317.4(1), b = 2491.4(1), c = 1190.6(1) pm, R1 = 0.0315). The hexaiodide complex cation 16+consists of a cyclo-Be3O 3 core with slightly distorted chair conformation, stabilized by coordination of two acetonitrile ligands at each of the beryllium atoms and by a Be(CH3CN)32+ cation at each of the oxygen atoms. This unique coordination behaviour results in coplanar OBe3 units with short Be-O distances of 155.0 pm and 153.6 pm on average of bond lengths within the cyclo-Be3O3 unit and of the peripheric BeO bonds, respectively. Exposure of compound 1·4CH3CN to moist air leads to small orange crystal plates of [Be(H2O) 4]I2·2CH3CN (3·2CH 3CN). According to the crystal structure determination (Space group C2/c, Z = 4, lattice dimensions at 100(2) K: a = 1220.7(1), b = 735.0(1), c = 1608.5(1) pm, β = 97.97(1)°, R1 = 0.0394), all hydrogen atoms of the dication [Be(H2O)4]2+ are involved to form O-H···N and O-H···I hydrogen bonds with the acetonitrile molecules and the iodide ions, respectively. Quantum chemical calculations (B3LYP/6-311+G**) at the model [Be 3(μ3-O)3(HCN)6Be(HCN) 33]6+ show that chair and boat conformation are stable and that the distorted chair conformation is stabilized by packing effects. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Acetonitrile complex; Beryllium; IR spectroscopy; Quantum chemical calculations; Tetraaqua complex; X-ray diffraction